IDEAS OF GLOBALISM IN HOLLYWOOD SITCOMS - Simovic, Vlade (Politeia, 2023)
Globalization is a process that has lasted for centuries. People naturally tend to cross state borders. Some from cultural motives of getting to know the world, others from economic ones, and others from political ones. Over time, the idea of globalism emerged. It implied a directed activity of global importation of the world with the aim of strengthening large corporations and their countries. These are primarily corporations and political elites of the United States. Those ideas of globalism are promoted and imported into the modern world through the creation of greater economic interdependence and de-sovereignization of states, through military and political domination, through new technologies, but also through culture and the media. In that context, Hollywood series also play an important role. By analyzing the content of the most watched Hollywood sitcoms, such as The House of Cards, The Americans, The Big Bang Theory and Two and a Half Men, this research determines which ideas of globalism these series promote and in what way. This raises the question of the importance of Western media and culture in the process of globalization of the world.
Keywords: Globalization; globalism; Hollywood sitcoms